Amino acid variations in polymorphic noble scallops, Chlamys nobilis. Issue 12 (22nd October 2019) - Tan, Kar Soon; Leng, Xuemei; Zhao, Yang; Hongxing, Liu; Cheng, Dewei; Ma, Hongyu; Li, Shengkan; Zheng, Huaiping
Abstract: Noble scallop Chlamys nobilis is an economically important edible marine bivalve that display polymorphism in shells and flesh colors. The present study was carried out to investigate whether there is a difference in amino acid (AA) content and composition between the two polymorphic scallops. The AA content and compositions of the whole edible flesh, adductor, and mantle were extracted and analyzed using high‐performance liquid chromatography. The results of this study revealed that golden and brown scallops have a similar AA composition, but distinctive content, and the differences in AA contents are obvious in adductor. Moreover, regardless of shells and flesh color, both noble scallops have high quantity and high‐quality proteins that are easily digested and contain dietary essential AAs in quantities corresponding to human requirements. The present study demonstrates for the first time that polymorphisms in aquatic animals have different AA contents but similar composition. Practical applications: The noble scallop is an economically important edible marine bivalve that is widely distributed in Japan, Indonesia, and the Southern Sea of China. They have been widely cultivated in South China since the 1980s. The present study not only provides knowledge of the AA composition of scallops which serves as a basis for establishing their potential nutritive value, but also provides the first reference for AA content and compositions of polymorphism.